Effect of the Presence of a Heat Conducting Horizontal Square Block on Mixed Convection inside a Vented Square Cavity - Rahman, Md. M. M.; Alim, M. A. A.; Saha, S.; Chowdhury, M. K. K. (Nonlinear Analysis: Modelling and Control, 2009)
Finite element method is used to solve two-dimensional governing mass, momentum and energy equations for steady state, mixed convection problem inside a vented square cavity. The cavity consists of adiabatic left, top and bottom walls and heated right vertical wall; but it also contains a heat conducting horizontal square block located somewhere inside the cavity. Forced flow conditions are imposed by providing an inlet at the bottom of the left wall and an exit at the top of the right wall, through which the working fluid escape out of the cavity. The aim of the study is to describe the effect of such block on the flow and thermal fields. The investigations are conducted for various values of geometric size, location and thermal conductivity of the block under constant Reynolds and Prandtl numbers. Various results such as the streamlines, isotherms, heat transfer rates in terms of the average Nusselt number, average fluid temperature in the cavity and the temperature at the center of solid block are presented for different parameters. It is observed that the block size and location have significant effect on both the flow and thermal fields but the solid-fluid thermal conductivity ratio has insignificant effect on the flow field. The results also indicate that the average Nusselt number at the heated surface, the average temperature of the fluid inside the cavity and the temperature at the center of solid block are strongly dependent on the configurations of the system studied under different geometrical and physical conditions.
Keywords: finite element method; square block; vented cavity and mixed convection